2004
DOI: 10.1086/421243
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal–Regulated Kinase Mediates Apoptosis Induced by UropathogenicEscherichia coliToxins via Nitric Oxide Synthase: Protective Role of Heme Oxygenase–1

Abstract: Pyelonephritis is a risk factor for renal tubular epithelial cell damage in children. The inter- and intracellular regulator nitric oxide (NO) plays a role in the modulation of cellular viability in urinary tract infections, but the role of the NO pathway in renal proximal tubular-cell death remains unclear. The present study demonstrates that, in renal epithelial cells undergoing death mediated by Escherichia coli strain ARD6 serotype O6K13H1 (O6), levels of the phosphorylated extracellular signal-regulated k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
3
31
1
Order By: Relevance
“…In addition, the inhibition of either NHE1 by amiloride or calpain by ZLLal blocked Bcl-2 degradation caused by LPS. These results strongly suggest that NHE1 is required for LPS-induced Endothelial cell injury is common in the pathogenesis of several diseases, including atherosclerosis [29] , hypertension [30] , and congestive heart failure [31] . During bacterial sepsis, endothelial cell death is the final step of a process that begins when quiescent endothelial cells are induced to express pro-coagulant, pro-adhesive, and vasoconstrictive factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibition of either NHE1 by amiloride or calpain by ZLLal blocked Bcl-2 degradation caused by LPS. These results strongly suggest that NHE1 is required for LPS-induced Endothelial cell injury is common in the pathogenesis of several diseases, including atherosclerosis [29] , hypertension [30] , and congestive heart failure [31] . During bacterial sepsis, endothelial cell death is the final step of a process that begins when quiescent endothelial cells are induced to express pro-coagulant, pro-adhesive, and vasoconstrictive factors.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that two stress-induced anti-apoptotic genes are up-regulated only when explants are cultured in the absence of hormones. The first gene, HMOX-1 is the rate-limiting enzyme in the catabolism of heme-generating biliverdin, carbon monoxide and iron (Alam et al 2000, Chen et al 2004, and is an inducible enzyme activated by most oxidative stress inducers and cytokines (Chen et al 2004). The almost universal stimulation of HMOX expression by pro-oxidants and the observation that biliverdin and bilirubin are potent anti-oxidants have led to the assumption that enhancement of HMOX activity represents an adaptive, and ultimately protective response to cellular stress (Alam et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The HMOX enzyme is believed to exert an anti-apoptotic action by decreasing intracellular pro-oxidant levels (Fang et al 2004). For example, in renal immune injury, it is proposed that activation of HMOX protects against NO-mediated toxicity by negatively modulating expression or activity of iNOS (Chen et al 2004). The second gene, TEGT suppresses apoptosis induced by bax, etopsoside, staurosporine and growth factor deprivation (Grzmil et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell lines (LLC-PK1 and OK) and primary cultures of renal proximal tubular cells, inhibition of ERK improved cell survival by inhibiting apoptosis after cisplatin exposure (Ishikawa and Kitamura, 2000;Nowak, 2002;Kim et al, 2005). The proapoptotic role of ERK in renal epithelial cells is not limited to cisplatin exposure; ERK activation is also associated with cell death induced by reactive oxygen species (ROS) (Tikoo et al, 2001;Ramachandiran et al, 2002;Dong et al, 2004), Escherichia coli toxins (Chen et al, 2004), zinc , and cephaloridine (Kohda et al, 2003). ERK activation also has been implicated in cell death induced by deprivation of survival factors.…”
Section: Erk Signaling Mediates Apoptosis In Cultured Cellsmentioning
confidence: 99%